Letter - National Federation of Building Trades Operatives, Tooting, 7 May 1926 (Tooting)
1926-05-07 "Letter - National Federation of Building Trades Operatives, Tooting, 7 May 1926" [g0236001.jpg], 7 May 1926 Local Organisation